2000
DOI: 10.1074/jbc.m006379200
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Laminin 5 by Keratinocytes Regulates Integrin Adhesion and Signaling

Abstract: Deposition of laminin 5 over exposed dermal collagen in epidermal wounds is an early event in repair of the basement membrane. We report that deposition of laminin 5 onto collagen switches adhesion and signaling from collagen-dependent to laminin 5-dependent. Ligation of laminin 5 by integrin ␣ 6 ␤ 4 activates phosphoinositide 3-OH-kinase (PI3K) signaling. This activation allows for adhesion and spreading via integrin ␣ 3 ␤ 1 on laminin 5 independent of RhoGTPase, a regulator of actin stress fibers. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
167
2
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(178 citation statements)
references
References 60 publications
5
167
2
4
Order By: Relevance
“…Laminin-332 has been reported to interact with integrin a3b1 or a6b4 and activate many signal mediators such as PI3K, focal adhesion kinase, protein kinase C, Rac, ERK, JNK and nuclear factor kB, leading to enhanced cell migration and invasion (Nguyen et al, 2000;Kariya and Miyazaki, 2004;Nikolopoulos et al, 2005). In particular, the importance of PI3K activation induced by laminin-332 during carcinogenesis or tumour invasion has been recently suggested (Marinkovich, 2007;Waterman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laminin-332 has been reported to interact with integrin a3b1 or a6b4 and activate many signal mediators such as PI3K, focal adhesion kinase, protein kinase C, Rac, ERK, JNK and nuclear factor kB, leading to enhanced cell migration and invasion (Nguyen et al, 2000;Kariya and Miyazaki, 2004;Nikolopoulos et al, 2005). In particular, the importance of PI3K activation induced by laminin-332 during carcinogenesis or tumour invasion has been recently suggested (Marinkovich, 2007;Waterman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In several types of carcinomas, laminin-332 has been reported to be highly expressed and to correlate well with poor patient prognosis (Pyke et al, 1995;Soini et al, 1996;Koshikawa et al, 1999;Matta et al, 1999;Ono et al, 1999;Yamamoto et al, 2001;Fukai et al, 2005). Laminin-332 is known to support cellular survival, proliferation and migration by activating many signal mediators through the ligation with a3b1 and a6b4 integrin, and to have important roles in tumour invasion and metastasis (Nguyen et al, 2000;Kariya and Miyazaki, 2004;Nikolopoulos et al, 2005). Particularly, the phosphatidylinositol 3-kinase (PI3K) activation induced by laminin-332 during carcinogenesis or tumour invasion has been highlighted (Marinkovich, 2007;Waterman et al, 2007).…”
mentioning
confidence: 99%
“…Importantly, Geuijen and Sonnenberg (40) showed that ␣6␤4-triggered motility inhibition was not simply due to increased adhesion to Ln-5 but was a result of increased stability of the interaction between ␣6␤4 and Ln-5. Thus, ␣6␤4-triggered simultaneous up-regulation of both cell-ECM and cell-cell adhesion may result in an adhesive, non-migratory phenotype and may explain the observation that Ln-5 can guide keratinocytes to switch from a migratory-to a dormant, integrated epithelial phenotype (11,41). Concerted substrate-and intercellular adhesion regulation is a prerequisite for tissue rearrangement during morphogenesis or remodeling (42).…”
Section: Discussionmentioning
confidence: 99%
“…This regulation of PI3K by integrin signaling has particular implications for ⌬Np63␣ expression. ⌬Np63␣ expression in the epidermis is limited to the basal layer of keratinocytes, which maintain contact with the basement membrane (12,13); certain integrin signaling pathways are highly active in these cells (32,53). Integrin-mediated activation of the PI3K pathway, therefore, may be partly responsible for the observed distribution of ⌬Np63␣ expression in the epidermis.…”
Section: Discussionmentioning
confidence: 99%